Arterial, Mixed Venous or Central Venous Hemogasometry and End Tidal CO2 in Dogs under Different Hemodynamic States - Gehrcke, Martielo Ivan (2017)
Background: Hemogasometric analysis is used in the interpretation of acid-base balance (ABB) and to access pulmonary ventilation. Already mixed venous oxygen saturation obtained at pulmonary artery correlates with tissue oxygenation. However, both samples can be difficult to access because of the difficulties in arterial and pulmonary catheterization. The aim of this study was to evaluate the feasibility of replacing the arterial and mixed venous bloods, the end tidal pressure of carbon dioxide (EtCO2) and central venous blood in the analysis of pulmonary ventilation, tissue oxygenation and ABB in dogs under different hemodynamic states.Material, Methods & Results: Nine dogs were used with an average weight of 19.6 ± 1.3 kg, anesthetized with isoflurane at 1.4 V% diluted on oxygen 60% (Baseline), and subsequently undergoing mechanical ventilation (MV) and the hypodinamic state (Hypo) with isoflurane at 3.5V% and mean arterial pressure (MAP) lower than 50 mmHg and hyperdynamic state (Hyper) by dobutamine infusion at 5 μg/kg/min and with MAP 30% higher than baseline. For each time allowed a 15 min of stabilization by each hemodynamic status. Simultaneously were collected samples of 0.6 mL of arterial blood by metatarsal artery, mixed and central venous blood by pulmonary artery and right atrium for hemogasometric analysis. To access lung function we correlated and compared the EtCO2 values obtained by gas analyzer with expired carbon dioxide pressure in the arterial blood (PaCO2), mixed venous blood (PmvCO2) and central venous blood (PcvCO2). For the interpretation of tissue oxygenation we correlated and compared the values of mixed (SmvO2) and central (ScvO2) venous oxygen saturation. For the acid-base balance we used the correlation of potencial hydrogen (pH); carbon dioxide pressure (PCO2); bicarbonate ion (HCO3-); base excess (BE); anion GAP (AG); sodium ions (Na+), chlorine ions (Cl-), potassium ions (K+) and ionized calcium (iCa) of arterial (a) mixed venous (mv) and central venous (CV) bloods. Statistical analysis was performed using ANOVA-RM followed by Dunnet test for differences between times and Tukey’s test for differences among the samples (P ≤ 0.05). Pearson correlation analysis was performed using linear regression and for comparison methods we used the Bland-Altman analysis The EtCO2 values correlated (r = 0.87) and were according to Bland-Altman analysis with PaCO2 values (mean difference of -1.6 ± 2,9 mmHg for PaCO2. There were no differences (P ≤ 0.05) from SmvO2 and ScvO2. ScvO2 correlated (r = 0.91) with SmvO2 at different hemodynamic states and with a mean difference of -0.4 ± 2.5%. Both venous bloods were correlated with the analysis of arterial blood acid-base balance and electrolytes in different hemodynamic states. However, the ionized calcium levels were 40% lower in arterial blood.Discussion: EtCO2 measurement depends of monitor technology and proper pulmonar ventilation and perfusion. In this study the limiting factor in replacing the PaCO2 hair EtCO2 was spontaneous ventilation because in this state pulmonary ventilation is compromissed. With the use of MV was possible get up similar results in the pulmonar function analysis using the EtCO2 and PaCO2. The use of central venous blood instead mixed venous blood at oxygen saturation analysis provided adequate estimate this parameter. This being easier and less invasive technique. ABB was possible with all samples with own reference values for venous and arterial samples. This is an interesting result for critical patients where the arterial sample is difficult. In electrolytes the sample was indifferent except for calcium because pH interfere in this values. It was conclude that the values of EtCO2 and central venous blood are correlated and can replace arterial and mixed venous bloods in the analysis of lung function, tissue oxygenation and acid base balance.